Preparation and water/oil separation of super‐hydrophobic biomass adsorbent based on three‐dimensional graphene aerogel. Issue 3 (10th December 2022) - Liu, Ting; Li, Dandan; Huang, Kangkang; Tan, Shaozao; Huang, Langhuan
Abstract: Water pollution caused by oil spills and organic solvents have seriously affected the quality of the environment, so the development of green and recyclable oil adsorbents with excellent properties has drawn massive attention from researchers. In this work, bamboo powder (BP) and reduced graphene oxide (GO) were used as raw materials to create a bamboo fiber/graphene aerogel (BGA) aerogel by a green one‐pot hydrothermal method. Then, a three‐dimensional aerogel super‐hydrophobic modified bamboo fiber/graphene aerogel ( H@BGA) with super‐hydrophobic properties and a high adsorption capacity was synthesized by using hexadecyltrimethoxysilane (HDTMS) as hydrophobic modification reagent. In this unique ternary aerogel, both bamboo powder and HDTMS could improve the hydrophobicity of the aerogel. Furthermore, the uniformly interspersed bamboo fibers facilitated the exfoliation of graphene, constructing abundant pores and endowing the sample with a large specific area and excellent mechanical properties. The as‐prepared H@BGA featured low density, high specific surface area, super‐hydrophobicity (WCA = 151.5°), and high adsorption capacity (55–123 g g −1 ). In addition, the adsorption capacity of H@BGA could remain above 95% after 8 cycles of the adsorption/desorption process. Overall, the aerogel has broad application prospects in the field of water/oil separation. © 2022 Society of Chemical Industry (SCI).